Radical gestures: feminism and performance art in North America - Wark, Jayne (McGill-Queen's University Press, 2006)
Wark brings together a wide range of artists, including Lisa Steele, Martha Rosler, Lynda Benglis, Gillian Collyer, Margaret Dragu, and Sylvie Tourangeau, and provides detailed readings and viewings of individual pieces, many of which have not been studied in detail before. She reassesses assumptions about the generational and thematic characteristics of feminist art, placing feminist performance within the wider context of minimalism, conceptualism, land art, and happenings
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; art contemporain; art féministe; arts; corps; cours; discipline; femmes* artistes; féminisme pop; har4600; histoire de l'art; histoire et politique; militance; performance; premier cycle; périodes historiques; régions géographiques; thématiques